ABCD1234pop 1 Posted March 10, 2013 Share Posted March 10, 2013 I know how to find A inverse. And I know ACA=AB. But how do I go through solving this? I figured it had something to do with the inverse of A. But matrix multiplication isn't the same as normal multiplication. Will something like (Inverse of A)ACA=(Inverse of A)B Since (Inverse of A)A=The identity Matrix CA=B Then CA(Inverse of A)=B(Inverse of A) C=B(Inverse of A) I'm pretty sure all of this is wrong, but even if it isn't, I'm stuck here. How can I solve this and similar questions? Link to post Share on other sites

timo 583 Posted March 10, 2013 Share Posted March 10, 2013 Straightforward plugging into the equation will show you that your result is a correct solution (it doesn't show that it is the only solution, though): [math]ACA - AB \stackrel{C=BA^{-1}}{=} AB\underbrace{A^{-1}A}_{=1} - AB = AB - AB = 0[/math] Link to post Share on other sites

## Recommended Posts

## Create an account or sign in to comment

You need to be a member in order to leave a comment

## Create an account

Sign up for a new account in our community. It's easy!

Register a new account## Sign in

Already have an account? Sign in here.

Sign In Now